Cardioversion of atrial fibrillation of recent onset with flecainide. Issue 789 (July 1991) - Carr, B.; Hawley, K.; Channer, K. S.
Abstract : Twenty-eight patients with atrial fibrillation of less than 1 month's duration were given a single intravenous bolus of flecainide (2 mg/kg). Nineteen patients (68%) were successfully converted to sinus rhythm. Of the 19 patients with atrial fibrillation of less than 72 hours duration, 18 (95%) were successfully converted. Failure to cardiovert was associated with cardiomegaly on chest X-ray and larger left atrial diameter measured echocardiographically. Of the 9 patients who failed to convert, 2 had biochemical evidence of thyrotoxicosis and chronic obstructive pulmonary disease. Of the 19 patients successfully cardioverted, the atrial fibrillation complicated acute myocardial infarction in 3 cases and a pulmonary embolism in one. Six cases occurred post-operatively and in 3 out of 6 the patient was ventilated. No side effects were observed. The use of intravenous flecainide should avoid the need for electrical DC conversion even in sick patients. Failure of conversion is associated with covert underlying predisposing factors and duration of atrial fibrillation of more than 72 hours.